La fécondité précoce dans les camps d’hébergement de l’Aire Métropolitaine de Port-au-Prince dans un contexte post-catastrophe naturelle - David Jean Simon; Ladeu Tokpa (Études Caribéennes)
The earthquake that occurred January 12, 2010 in Haiti has changed demographic situation of the country. These demographic changes also have negative impacts on adolescent’s fertility, particularly on those living in accommodation camps. According to DHS (2012), adolescent fertility rate has very increased (66‰ in 2012; 44,35‰ in 2009). In comparison with other cities or areas of the country, adolescents living in the camps have the higher fertility’s rate (107‰). The aim of this paper is to identify social, cultural, demographic factors explaining adolescent fertility living in the camps.Data that we used in this paper come from Demographic and Health’s survey (Haiti, 2012). Moreover data analysis has been performed at two different levels: descriptive analysis and multivariate analysis and we have found that the “presence children 5 and under in household”, the “age at first sex”, the “marital status” and the “education level” are key factors in explaining adolescent fertility in accommodation camps.